2021
DOI: 10.1021/acs.jpclett.1c03851
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Biphenylene: A Graphene Allotrope with Superior Activity toward Electrochemical Oxygen Reduction Reaction

Abstract: Developing efficient and inexpensive catalysts for the oxygen reduction reaction (ORR) is a key for sustainable development of fuel cell technologies. Herein, by means of density functional theory calculations and microkinetic modeling, we demonstrate that two-dimensional (2D) biphenylene, a recently synthesized allotrope of graphene composed of tetragonal, hexagonal, and octagonal rings, is a metal-free candidate for facilitating the electrochemical ORR. Different from semimetallic graphene, 2D biphenylene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…Specically, the total energy of the charged slab at the corresponding potential, E(U), was calculated by including energy corrections for it is necessary to add or remove electrons and background charge on the electronic energy obtained from self-consistent calculations. [45][46][47][48][49] Then, for each species, we can deduce the energy at a given potential by tting the ve energy-potential points in a quadratic form.…”
Section: Constant-potential Computationsmentioning
confidence: 99%
“…Specically, the total energy of the charged slab at the corresponding potential, E(U), was calculated by including energy corrections for it is necessary to add or remove electrons and background charge on the electronic energy obtained from self-consistent calculations. [45][46][47][48][49] Then, for each species, we can deduce the energy at a given potential by tting the ve energy-potential points in a quadratic form.…”
Section: Constant-potential Computationsmentioning
confidence: 99%
“…Based on the experimental realization, Li's group conducted a theoretical study on the catalytic activity of 2D biphenylene for the oxygen reduction reaction (ORR), and revealed that biphenylene is a metal-free ORR electrocatalyst with high activity. 31 Most recently, Obeid and Sun designed a biphenylene-based 3D porous carbon allotrope, which can serve as a promising anode material for LIBs. 32 In terms of the performance of the newly synthesized biphenylene as an anode for SIBs, herein we carried out comprehensive density functional theory (DFT) calculations as implemented in the Vienna Ab initio Simulation Package (VASP).…”
mentioning
confidence: 99%
“…Based on the experimental realization, Li's group conducted a theoretical study on the catalytic activity of 2D biphenylene for the oxygen reduction reaction (ORR), and revealed that biphenylene is a metal-free ORR electrocatalyst with high activity. 31 Most recently, Obeid and Sun designed a biphenylene-based 3D porous carbon allotrope, which can serve as a promising anode material for LIBs. 32…”
mentioning
confidence: 99%
“…BPN also has excellent stability and mechanical performance, [31][32][33] and its thermal transport is lower than graphene. 34,35 In addition, BPN can be used in optoelectronics and electronics, 36 in catalysts for the oxygen reduction reaction (ORR) 37 and in anode materials for batteries. [38][39][40] Although some preliminary explorations have been performed on BPN, a more detailed understanding is still lacking, and the effect of heteroatoms on its catalytic activity in particular has not been widely explored.…”
Section: Introductionmentioning
confidence: 99%